Amorphous photonic crystals and structural colors in the phase separation glaze. Issue 4 (April 2018) - Shi, Pei; Wang, Fen; Zhu, Jianfeng; Yang, Haibo; Wang, Yi; Fang, Yuan; Zhang, Biao; Wang, Jiahuan
Abstract: In this paper, the phase-separated structures and the effective refractive index of the sky-blue glaze of Jun ware were investigated to determine the forming conditions of structural colors caused by amorphous photons crystals. It showed that with separation structures of short range order and average diameter of 106–260 nm, the structural color of amorphous photons could be formed in the glaze. In order to verify them and study the effect of colorant by the experimental method, the phase separation glazes were prepared with different contents of iron ore slag. The results indicated that the addition of colorant not only increased the effective refractive index of glazes, but also darkened the glaze color and suppressed incoherent scattering. Therefore, structural colors deepened with the increasing of colorant contents. Deciphering the ancient nanotechnology could thus potentially help researchers prepare colorful glazes by the green environmental protection method.